1987
DOI: 10.4269/ajtmh.1987.37.534
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Chronic Murine Trypanosoma cruzi Infection and Pregnancy: Fetal Growth Retardation

Abstract: Fetal growth, reproductive capacity, and parasitemia were studied in three groups of BALB/c mice: pregnant and chronically infected with Trypanosoma cruzi, non pregnant but similarly infected, and pregnant but noninfected. The pregnant mice were killed on day 17 of pregnancy. Comparisons of the two pregnant groups showed significant differences in fetal weights and x 18 magnified ossification lengths of radius and cubitus, whereas placental weights were not modified. The results indicate that intrauterine grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Experiments with mice and rats inoculated with parasites at different times before or during gestation showed either none or rare maternal-fetal transmission (Apt et al, 1968a,b;Werner and Egger, 1971;Cabeza et al, 1980;de Cunio et al, 1980;Andrade, 1982;Carlier et al, 1987;Davila et al, 1994;Gonzalez Cappa et al, 1999;Mjihdi et al, 2002;Solana et al, 2002;Moreno et al, 2003;Alarcón et al, 2009). However, transmission occurred when a blockade of placental phagocytic activity or placental lesions were induced (Werner and Kunert, 1958;Delgado and Santos-Buch, 1978).…”
Section: Parasite Diversity and Congenital Transmission In Experimentmentioning
confidence: 94%
“…Experiments with mice and rats inoculated with parasites at different times before or during gestation showed either none or rare maternal-fetal transmission (Apt et al, 1968a,b;Werner and Egger, 1971;Cabeza et al, 1980;de Cunio et al, 1980;Andrade, 1982;Carlier et al, 1987;Davila et al, 1994;Gonzalez Cappa et al, 1999;Mjihdi et al, 2002;Solana et al, 2002;Moreno et al, 2003;Alarcón et al, 2009). However, transmission occurred when a blockade of placental phagocytic activity or placental lesions were induced (Werner and Kunert, 1958;Delgado and Santos-Buch, 1978).…”
Section: Parasite Diversity and Congenital Transmission In Experimentmentioning
confidence: 94%
“…To obtain maximum fecundation rates at the time of mating, females were maintained in anestrus before mating by keeping them for 2 weeks in a different room from the males. 12 To synchronize the menstrual cycles at the time of mating, females infected 4 days previously, and uninfected age-matched controls, were placed for 2 days in cages in which the litter had been impregnated with the odor of males (ie, cages having contained males). On day 6 after infection in the afternoon, one uninfected male was added, per cage containing two females, and the presence of a vaginal plug, indicating that mating had occurred, was checked every morning for 4 days.…”
Section: Mice T Cruzi Infection and Matingmentioning
confidence: 99%
“…Infertility and fetal growth retardation, associated or not with congenital infection, have been reported in chronic infection of mice. 12,13 In acute experimental infection, placental infection has been reported without congenital transmission, 14 despite the high circulating level of parasites, known to release proinflammatory molecules 15,16 and the systemic production of cytokines potentially deleterious for pregnancy. 17,18 The aim of the present work was to gain more insight into the relation between acute T. cruzi infection and gestation in mice, by studying the reproductive capacity, the pregnancy outcome, and the histopathology of uteroplacental units (UPUs) and fetuses in relation to maternal parasitic load.…”
mentioning
confidence: 99%
“…Retarded fetal growth associated or not with congenital infection has been reported to occur in chronically infected mice (Carlier et al, 1987;Gonzalez et al, 1999). Hermoso et al (2001) also observed that placental diameter was reduced in animals infected with the RAL strain of T. cruzi.…”
Section: Discussionmentioning
confidence: 99%